Spillover Effects in Green and Traditional Assets During Global Crises: Evidence from TVP-VAR Analysis - Chiaka, Felicia; Deanita, Gwenda; Fauzi, Fitriya (International Journal of Energy Economics and Policy, 2025)
This paper employs the Time-Varying Parameter Vector Autoregression (TVP-VAR) model to analyze return and volatility spillovers, along with portfolio implications, across Green Bonds (GB), ESG stocks, the clean energy index (SP_CE), green cryptocurrencies (ADA, IOTA, XRP), Bitcoin (BTC), and gold. The study covers the COVID-19 pandemic and the Russia-Ukraine war. Results show a significant rise in total return and volatility connectedness during these crises, suggesting that global shocks heighten market interdependence. ESG stocks emerge as net transmitters of both return and volatility spillovers, while green cryptocurrencies (excluding ADA) are net receivers of volatility. Bitcoin exhibits asymmetric behavior—acting as a return transmitter but becoming a volatility receiver in crisis periods. Traditional assets such as gold, green bonds, and clean energy stocks remain net receivers in both return and volatility channels, underlining their defensive nature and potential role as hedging instruments during periods of turmoil.